2023
DOI: 10.1371/journal.pone.0279930
|View full text |Cite
|
Sign up to set email alerts
|

Potential of using facial thermal imaging in patient triage of flu-like syndrome during the COVID-19 pandemic crisis

Abstract: The screening of flu-like syndrome is difficult due to nonspecific symptoms or even oligosymptomatic presentation and became even more complex during the Covid-19 pandemic. However, an efficient screening tool plays an important role in the control of highly contagious diseases, allowing more efficient medical-epidemiological approaches and rational management of global health resources. Infrared thermography is a technique sensitive to small alterations in the skin temperature which may be related to early si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For the objective of recognizing faces and masks and allowing an efficient automated Covid-19 screening strategy in public setting using NTIC dataset. Makino et al [17] proposed to assess the abilities of infrared imaging, also known as thermography, to evaluate symptoms and early indications using thermal video frames of different face regions of people, and then analyze their body temperature as a diagnostic tool to aid screening. 136 patient samples were gathered and examined at the emergency room of the aforementioned hospital from June to September 2022 in accordance with the inclusion and exclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…For the objective of recognizing faces and masks and allowing an efficient automated Covid-19 screening strategy in public setting using NTIC dataset. Makino et al [17] proposed to assess the abilities of infrared imaging, also known as thermography, to evaluate symptoms and early indications using thermal video frames of different face regions of people, and then analyze their body temperature as a diagnostic tool to aid screening. 136 patient samples were gathered and examined at the emergency room of the aforementioned hospital from June to September 2022 in accordance with the inclusion and exclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the need to assess additional physiological parameters to increase the sensitivity and specificity of non-invasive biosensors [ 14 ]. However, more recently, Makino Antunes et al reported a predictive model that reached an accuracy of 86% for disease detection [ 15 ]. In addition to the traditional measurement of temperature by infrared methods, there have been reports of algorithms based on artificial intelligence and the use of drones with thermal cameras for temperature measurement and algorithms to recognize human actions such as coughing and sneezing, which are paramount symptoms of respiratory infections [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…NCITs measure temperature at a single point using a sensor with one or a few pixels. On the other hand, IRTs provide a temperature map of a large area using a sensor with thousands of pixels, which allows for greater flexibility in assessing different regions of the face and improves the effectiveness of temperature estimation [ 10 , 11 ]. Recent studies and evidence in the literature suggest that qualified IRTs, when used properly, can offer superior accuracy in estimating EBT compared to NCITs [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%